Combination of stem cell-derived secretome from human exfoliated deciduous teeth with Yemeni Sidr honey on cell viability and migration: an in vitro study - Mona Abdulrahman Abdullah Al-Hadi (Nature Publishing Group, 2024)
Abstract Introduction Bone diseases have a profound global impact, especially when the body's innate regenerative capacity falls short in the face of extensive damage. Stem cells from human exfoliated deciduous teeth (SHEDs), discovered in 2003, offer a promising solution for tissue repair, as they self-renew naturally and are easily obtainable. Mesenchymal stem cells (MSCs), including SHEDs, are believed to promote tissue regeneration by releasing growth factors, collectively known as the secretome. Aims This study explored the potential of combining SHED-derived secretome with Yemeni Sidr honey to improve osteoblast and fibroblast cell viability and migration. Materials and methods The experiment involved treating cell cultures of two types of rat cell lines - 7F2 osteoblast and BHK-21 fibroblast immortalized cells - with SHED-derived secretome and Yemeni Sidr honey. After the treatment, cell viability was measured using the MTT assay, which calculates OD at 590 nm. Additionally, the scratch assay was conducted to evaluate cell migration, and ImageJ software was used for data processing. Results The findings indicated that combining SHED-derived secretome and Yemeni Sidr honey enhanced osteoblast and fibroblast cell viability and migration. Furthermore, the study highlighted the difference in the stimulative potential of SHED-derived secretome, Yemeni Sidr honey, and their combination, on the viability and migration of the cultured cells. Conclusion The research concludes that combining SHED-derived secretome with Yemeni Sidr honey has the potential to promote cell viability and migration in in-vitro settings. The synergistic application of these substances has been found to be more effective -when combined in a dose-dependent manner- than their counterparts. Overall, the current study serves as a foundation for further investigations to establish if the explored substance has any useful clinical applications.